Pengembangan panduan konseling kelompok menggunakan teknik modeling untuk meningkatkan self-management - Maria Natalia Loban; Merita F. Naisanu; Lebrina T. Sole (Global Econedu, 2024)
This research aims to produce a group counseling guidelines using modeling techniques to improve self-management. The method used in this research is the research and development method. This guidelines was validated by two expert validators with a background in guidance and counseling and languages, as well as by one practitioner validator with a background in guidance and counseling education. The sampling technique used was purposive sampling which was adapted to the research objectives. The number of samples in this study was 5 people, adjusted to the number of counseling group members, namely 2-8 people. Based on the guidelines that have been developed, the research results show that there is an increase in self-management with an average increase based on post test results of 42.4%. Thus group counseling uses effective modeling techniques to improve self-management.